2017
DOI: 10.3390/vetsci4040064
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Disorders and Leptospirosis: A Case Study in a Mixed-Species Farm (Cattle and Swine)

Abstract: Animal leptospirosis, exempt in rodents, manifests as peculiar biology where the animal can function, simultaneously or not, as a susceptible host or reservoir. In the first case, clinical symptoms are likely. In the second case, infection is subclinical and manifestations are mild or absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…This article is protected by copyright. All rights reserved reproductive tract, this chronic form determines important reproductive disorders, leading to impacting economic losses (Mori et al, 2017). Loureiro and Lilenbaum (2020) recently suggested that the silent reproductive form of leptospirosis should be considered as a specific syndrome, so called Bovine Genital Leptospirosis (BGL).…”
Section: Accepted Articlementioning
confidence: 99%
See 2 more Smart Citations
“…This article is protected by copyright. All rights reserved reproductive tract, this chronic form determines important reproductive disorders, leading to impacting economic losses (Mori et al, 2017). Loureiro and Lilenbaum (2020) recently suggested that the silent reproductive form of leptospirosis should be considered as a specific syndrome, so called Bovine Genital Leptospirosis (BGL).…”
Section: Accepted Articlementioning
confidence: 99%
“…Loureiro and Lilenbaum (2020) recently suggested that the silent reproductive form of leptospirosis should be considered as a specific syndrome, so called Bovine Genital Leptospirosis (BGL). It is most often caused by adapted strains from the Sejroe serogroup, and is associated to early embryonic losses and consequent estrus repetition, very probably due to uterine inflammation and/or direct invasion of the embryo by leptospires (Mori et al, 2017;Libonati et al, 2018). More recently, it was demonstrated a high oxidative damage in sheep infected with leptospires, contributing to reproductive disturbance pathophysiology .…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The disease has been reported in many parts of the world with variable prevalence rates ranging from 3% to 50% [2,3]. It results in significant negative impact on health and production of livestock due to the high cost of treatment and prevention programs, loss of milk production, abortion, repeated breeding, stillbirth, and retained placenta [4,5]. Clinically, affected animals may be asymptomatic carriers; however, some animals may show fulminant disease characterized by fever, jaundice, pink stained milk, hemoglobinuria, and death [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, this disease is characterised mainly by reproductive problems such as infertility, prolonged intervals between births, abortion and occurrence of stillbirths, leading to important economic losses [4, 5]. Recently, this agent has been identified in the uterus of non-pregnant cows, and infection of the reproductive tract may be the most important manifestation in pathogenesis of bovine leptospirosis [6].…”
Section: Introductionmentioning
confidence: 99%